Assessment of Morphological Attributes of Sago Palm Accessions of Aimas, Sorong, West Papua, Indonesia - Fathnoer, Veronica; Bintoro, Mochamad Hasjim; Lubis, Iskandar (Department of Agronomy and Horticulture, IPB University, 2020)
Sago palm has the highest starch content compared to the other source of carbohydrate crops such as cereal and tuberous crops. Sago palm can produce about 200-400 kg per trunk after 7 to 10 years. This research aimed to characterize several sago palm accessions in Aimas, Sorong District, West Papua Province, Indonesia. Eight sago palm accessions were studied, Waruwo, Wasulagi, Wasenan, Wayuluk, Wagelik, Wanegles, Wawun and Wafabala. Among these accessions, there were many diff erences based on trunk morphological characteristics which includes trunk height, diameter, circumference, and bark thickness, leaf number, length of rachis, length of petiole, and spine. Five accessions with potential yield of more than 200 kg dry starch per sago trunk are Waruwo, Wasulagi, Wasenan, Wayuluk and Wagelik. Stem morphological characters aff ect palm sago production, because the starch is located in the pith of the stem.